Etika Profesional dan Tanggung Jawab Ilmuwan dalam Kajian Profetik - Rahmi, Siti; Miftahul Jannah, Rumaysah; Amrillah, Rizki; Rasyidah, Arifah (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2024)
The scholars of knowledge are considered as those who fight for the prophets, thus making them the most honored people. Therefore, they have the obligation to pass on their knowledge and teach humanity to guide them on the path of Allah. Professional ethics are the behaviors of someone who strives to produce quality work in their career. A scientist is said to be professional if they can make good judgments about what is beneficial and what is harmful. Scientists are responsible for their knowledge, regardless of whether it benefits or harms society. This article examines the professional ethics and responsibilities of a scientist in relation to prophetic qualities. The article uses the literature review research method by gathering quotations from books and journals. The research results in defining a scientist based on various Islamic perspectives, defining professional ethics of a scientist, prophetic qualities as the foundation of a scientist's professional ethics, and the social role of scientists in human responsibilities.